PENERAPAN PROFILE MATCHING PADA SISTEM PENDUKUNG KEPUTUSAN PENGANGKATAN KARYAWAN TETAP DI PT. PROPAN RAYA ICC CABANG JAMBI: Decision Support System;Profile Matching;PHP;PHPMyAdmin;Permanent Employee. - Kahar, Novhirtamely; Wahyuning Astuti, Reny; Farida Nasution, Renny (JURNAL AKADEMIKA, 2021)
Human resources are the most important contribution to the growth and development of the company. For this reason, companies need to assess the performance of contract employees to be appointed as permanent employees so that their resources are of higher quality. At PT. Propan Raya ICC Jambi Branch selects permanent employees in a gradual period according to the length of the training period and other assessments, but sometimes it is not optimal in its implementation because it looks unprofessional and subjective. This study aims to build a decision support system application for permanent employee selection based on the criteria of creativity, work attitude (performance), and behavior. This application is built with support for PHP, CSS, and the PHPMyAdmin programming language. Input data is in the form of employee identity data, employee criteria and sub-criteria values ​​to be selected, through a calculation process using the profile matching method with the final employee ranking results. Information in the form of reports on the selection results of the appointment of contract employees to become permanent employees, employees selected to extend the contract period, and reports of contract employees who have quit. The implementation of the decision support application program for contract employee selection results showed that the recommended contract employee to be appointed as a permanent employee was Kamaludin with a score of 4,568 who had the highest score among other employees. From the results of this study it was concluded that this application was made to help PT. Propan Raya ICC Jambi Branch in implementing a decision support system with the profile matching method in processing employee data, especially facilitating the selection process for permanent employees.